2020
DOI: 10.22541/au.158921572.28585651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Respiratory Outcomes Following Cardiac Surgery in Patients with COVID-19

Abstract: The objective of this study was to describe early respiratory outcomes of asymptomatic COVID-19 patients after cardiac surgery. In this retrospective clinical study (case series) we reviewed and analyzed patient clinical data of 25 covid-19 asymptomatic patients that underwent urgent or emergent cardiac surgery between February 29 and April 10, 2020 in Tehran Heart Center Hospital. Median of age was 63 years (IQR, 52-67), Euro SCORE 7.50 (IQR, 6.5-8.5) and body mass index 26.3 (IQR, 22.5-28.6). 68% of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…The results presented by Bonalumi and colleagues are similar to those reported in other surgical services amongst COVID-19 patients in Italy 6 , as well as analyses of cardiac surgical patients with COVID-19 at other centres. [7][8][9] The summation of the available evidence points towards the serious consideration clinicians must give to deferring non-emergent cardiac surgery of COVID-19 patients, particularly amongst those with advanced age or sub-optimal pulmonary function.…”
Section: Manuscriptmentioning
confidence: 99%
“…The results presented by Bonalumi and colleagues are similar to those reported in other surgical services amongst COVID-19 patients in Italy 6 , as well as analyses of cardiac surgical patients with COVID-19 at other centres. [7][8][9] The summation of the available evidence points towards the serious consideration clinicians must give to deferring non-emergent cardiac surgery of COVID-19 patients, particularly amongst those with advanced age or sub-optimal pulmonary function.…”
Section: Manuscriptmentioning
confidence: 99%
“…Unfortunately, classifying cardiac surgery patients is a double-edged sword since they have some comorbid diseases, such as diabetes and hypertension, that increase the risk of Covid-19. Mortality and morbidity rates in patients confirmed with Covid-19 who had ST-segment elevation [Bangalore 2020;Giulio 2020] or cardiac surgery [ Barkhordari 2020] have been reported in a limited number of reports. Barkhordari et al reported that outcomes of urgent cardiac surgery in patients confirmed with Covid-19 were poor, and serious respiratory complications rates were high when compared with similar patients in the pre-pandemic period (2% vs. 16%) [ Barkhordari 2020].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic is not only associated with marked global morbidity and mortality, but also poor outcomes after cardiac surgery. 1 In this setting, an effective preoperative screening tool is necessary to optimize cardiac surgical outcomes, especially among asymptomatic patients who may be SARS-CoV-2 positive by reverse transcriptase polymerase chain reaction (RT-PCR).…”
mentioning
confidence: 99%